GIS-material for the archaeological project: Herstadberg manor - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the expansion of Ingelsta golf club the Swedish National Heritage Board's Contract Archaeology Division, UV Öst, has performed a field evaluation by Herstadberg manor, Kvillinge parish, Norrköping municipality. The evaluation showed that merely insignificant remains of past times' activity were preserved at the site of the manor.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the filed evaluation was to conclude to what extent parts of the site of the medieval village Herstadberg, that are now planned for development, contain any preserved remnants. The survey area also includes locations topographically suited for settlement and burials from other time periods, and the aim of the investigation was also to determine whether any such archaeological remains occur in the area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har genomfört en arkeologisk förundersökning vid Herstadbergs gård, Kvillinge sn, Norrköpings kommun, med anledning av Ingelsta golfklubbs planerade ombyggnad. Undersökningen visade att endast obetydliga lämningar efter äldre tiders aktiviteter fanns bevarade där det gamla säteriet Herstadberg har legat.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med undersökningen var att undersöka i vilken utsträckning de delar av Herstadbergs bytomt som kan komma att exploateras innehåller äldre bevarande lämningar. Undersökningsområdet innehåller även topografiskt fördelaktiga lägen för gravar och boplatser från andra tidsperioder och undersökningen skulle även syfta till att klargöra om sådant förekommer.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Herstadbergs gård
Keywords: historical period; historisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi